Type, Content, and Source of Social Support Perceived by Women during Pregnancy: Evidence from Matlab, Bangladesh (Journal of Health, Population and Nutrition, 2011)
Specific and contextualized data on social support during distinct health events are needed to improve social support interventions. This study identified the type, content, and source of social support perceived by women during pregnancy. In-depth interviews with 25 women, aged 18-49 years, living in Matlab, Bangladesh, were conducted. The findings demonstrated that women perceived, the receipt of eight distinct types of support. The four most frequently-mentioned types included: practical help with routine activities, information/advice, emotional support and assurance, as well as the provision of resources and material goods. Sources varied by type of support and most frequently included--mothers, mothers-in-law, sisters-in- law, and husbands. Examples depicting the content of each type of support revealed culturally-specific issues that can inform community-based social support interventions. Key words: Cross-sectional studies; Pregnancy; Qualitative studies; Reproductive health; Retrospective studies; Social support; Stress; Bangladesh   DOI: http://dx.doi.org/10.3329/jhpn.v29i2.7859 J HEALTH POPUL NUTR 2011 Apr;29(2):163-173